2010
DOI: 10.3810/hp.2010.11.347
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistance in Hispanic Patients Hospitalized in San Antonio, TX with Community-Acquired Pneumonia

Abstract: Limited information is available on the antimicrobial resistance of patients with community-acquired pneumonia (CAP) depending on their ethnicity. Our aim was to compare the clinical characteristics, etiology, and microbiological resistance of Hispanic versus non-Hispanic white patients. A retrospective cohort of 601 patients with a diagnosis of CAP included 288 non-Hispanic whites and 313 Hispanics. Penicillin-resistant Streptococcus pneumoniae was more common among Hispanic patients (21.7% vs 0%; P=0.03) but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…An additional finding of some concern is that the highest proportion of colistin resistance among those specimens, whose location of origin was reported in the database, was the outpatient setting (6.6% compared to 5.4% in the ICU specimens, for example). Although these infections would likely meet the definition for healthcare‐associated infection, AB as a community‐acquired respiratory pathogen is not unprecedented either in the United States or abroad . It is, however, reassuring that most other antimicrobials examined in our study exhibit higher rates of susceptibility in the specimens derived from the outpatient settings than either from the hospital or the nursing home.…”
Section: Discussionmentioning
confidence: 61%
“…An additional finding of some concern is that the highest proportion of colistin resistance among those specimens, whose location of origin was reported in the database, was the outpatient setting (6.6% compared to 5.4% in the ICU specimens, for example). Although these infections would likely meet the definition for healthcare‐associated infection, AB as a community‐acquired respiratory pathogen is not unprecedented either in the United States or abroad . It is, however, reassuring that most other antimicrobials examined in our study exhibit higher rates of susceptibility in the specimens derived from the outpatient settings than either from the hospital or the nursing home.…”
Section: Discussionmentioning
confidence: 61%
“…Hispanic patients have been reported to present a higher frequency of infection from Streptococcus pneumoniae resistant to penicillin. 60…”
Section: Ethnicitymentioning
confidence: 99%
“…Ten cohorts in twelve publications reported Hispanic as an ethnicity ( Table 4 ). 14,17,22,24,25,30,37,40,47,51,61,63 MRSA or S. aureus was reported in eight studies with conflicting results, E. coli was reported in three with two reporting higher risk in Hispanic persons, K. pneumoniae was reported in one, P. aeruginosa in one, SSTI in one, and UTI in one.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies included Hispanic individuals but did not investigate this relationship. 24,30,61 Three studies reported E. coli infections in Hispanic persons. 22,61,63 One pediatric study reported that Hispanic children were at a higher risk than non-Hispanic children for E. coli UTIs that were non-susceptible to first-generation cephalosporin antibiotics.…”
Section: Hispanic Vs Non-hispanic Personsmentioning
confidence: 99%